PENGARUH PERUBAHAN LAHAN SAWAH TERHADAP PRODUKSI PADI DI KABUPATEN CIANJUR, JAWA BARAT (2013-2023) - Wulandari, Dwi Putri; Handawati, Rayuna; Zid, Muhammad (J SIG (Jurnal Sains Informasi Geografi), 2025)
The decrease in the area of rice fields in Cianjur Regency over the last ten years was 20,687.15 hectares (ha), or 5.73%. This decrease in rice fields is inversely proportional to the increase in residential and industrial land. The area of residential land increased by 33,375.43 ha (9.24%), while industrial land expanded by 3,006.45 ha (0.83%). The reduction in rice field area was accompanied by a decline in rice production of 438,984 tons. This raises the issue of the impact of changes in rice field area on rice production. The purpose of this study was to determine the effect of changes in rice field area on rice production in Cianjur Regency from 2013 to 2023. The research problem was addressed using a quantitative geographic method with simple linear regression analysis. Data analysis utilized Landsat 8 imagery with a supervised classification technique, focusing on two variables: changes in rice field area (x) and rice production (y). The findings concluded that 67.2% of the decline in rice production was due to the reduction in rice field area, while 32.8% was influenced by other factors such as rainfall, altitude, irrigation, and fertilizer use. In the significance test analysis, a value of 1.81 > 1.00000 was obtained, with a research accuracy of 90.9%, indicating that the hypothesis was accepted. The regression analysis yielded the equation Y = -7.6 + 7.9(x) , meaning that rice production decreases by 7.6 tons for every 1 ha  reduction in rice field area.